Voices from Indonesian Legislative on Religious Education Policy - Jamhari, Jamhari; Nisa, Yunita Faela (Studia Islamika, 2021)
Religious violent extremism remains a problem for Indonesia. Recently, three consecutive attacks carried out by violent religious extremists — a suicide bombing in front of a Cathedral Church in Makassar South Sulawesi, the discovery of several prepared high explosive bombs in Condet Jakarta, and a female lone wolf attack on the Indonesian Police Criminal Investigation Agency — shocked the public (Fakta-data di Balik Bom Bunuh Diri, 29 Maret 2021; Polisi sebut Terduga Teroris Condet & Bekasi, 2021; Teroris Penyerang Mabes Polri, 2021). It may not be surprising since there were some early indications from various studies that some Indonesian people still have religious attitudes and behaviors that are exclusive, closed, anti-citizenship, anti-state, and even pro-violence (PPIM, 2016, 2017, 2018; Puspidep, 2017, 2018). The PPIM study results (2018) show that around 58.5 percent of students tend to be religious radical, and 51.1 percent tend to be intolerant to differences within Muslim groups. Then, as many as 34.3 percent of students are intolerant to non-Muslim groups. Radical views that are intolerant toward those who are different are the first step to violent extremism. These studies are a reminder that violent extremism is a problem for all of Indonesian society. Therefore, PPIM surveyed the perceptions of the public, students, teachers, and Indonesian Members of Parliament on violent extremism.